2020
DOI: 10.1002/jbm.b.34659
|View full text |Cite
|
Sign up to set email alerts
|

Tooth sealing formulation with bacteria‐killing surface and on‐demand ion release/recharge inhibits early childhood caries key pathogens

Abstract: Herein, we investigated a biointeractive tooth sealing material consisted of dimethylaminohexadecyl methacrylate (DMAHDM) and amorphous calcium phosphate nanoparticles (NACPs) to address the above issues simultaneously. Of note, 5% DMAHDM was incorporated into the resin blend, and 20% NACP was added to inorganic filler content of dental formulations intended as dental sealants. The sealing materials were used to seal human extracted teeth. The sealed teeth were subjected to an early childhood caries (ECC) key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…This study supported the finding of previous studies which revealed that experimentally developed bioactive pit and fissure sealants could resist the demineralization effect of bacterial acids and/or demineralizing solutions compared to non-bioactive sealants [ 27 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study supported the finding of previous studies which revealed that experimentally developed bioactive pit and fissure sealants could resist the demineralization effect of bacterial acids and/or demineralizing solutions compared to non-bioactive sealants [ 27 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, studies have been actively developing and investigating new bioactive materials and their anti-cariogenic effects and mechanical properties [ 22 , 23 , 29 , 35 , 36 ]. Only a few studies have studied the performance of recently introduced bioactive resin-based sealants.…”
Section: Introductionmentioning
confidence: 99%
“…Common methacrylates used to formulate restorative materials, such as triethylene glycol dimethacrylate (TEGDMA) and bisphenol A-glycidyl methacrylate (Bis-GMA), do not present antimicrobial activity [ 12 ]. The antimicrobial property could improve enamel caries prevention by reducing biofilm formation [ 13 ], which may positively impact patients with a high risk of caries that are not being benefited from enamel infiltration [ 14 ]. Antimicrobial agents have been added to resin infiltrants to improve their biological properties and increase their protective effect.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, biointeractive dental materials incorporated with antimicrobial and ion releasing/recharging formulations have been explored for the efficacy in interfering C. albicans-S. mutans biofilm formation. Incorporation of dimethylaminohexadecyl methacrylate (DMAHDM) and amorphous calcium phosphate nanoparticles (NACPs) into dental sealants showed promising effect on inhibiting C. albicans-S. mutans dual-species biofilm formation and preventing enamel mineral loss in vitro (76). Thus, using these selective materials may have beneficial effect in inhibiting C. albicans-S. mutans biofilm formation.…”
Section: Approaches To Disrupt C Albicans-s Mutans Biofilmmentioning
confidence: 99%